Developing P(MMA-co-NVP) hydrogels for use in self-inflating, anisotropic tissue expanders - Smith, JR (2015)
Artificial tissue expansion is required to generate new skin prior to reconstructive surgery, in order to compensate for a deficit of healthy tissue. Hydrogel tissue expanders, which expand anisotropically, show great promise in overcoming clinical limitations in the field, thus allowing the technique to be used in a wider range of surgeries. These devices consist of pellets of dry poly(methyl methacrylate-co-vinylpyrrolidone), compressed into discs through a hot compression moulding process. However, a number of significant problems still exist in these devices, and this thesis aims to address these issues.